Innovative thermal control of fermentations through the use of phase change materials: A focus on wine fermentation - Piernicola Masella; Giulia Angeloni; Ferdinando Corti; Agnese Spadi; Francesco Garbati Pegna; Lorenzo Guerrini; Alessandro Parenti (Applied Food Research)
The study aimed to investigate the feasibility of using Phase Change Materials (PCM) for temperature management during grape must fermentation, providing insights into potential energy-saving strategies in winemaking processes. The setup and procedure of fermentation tests at lab-scale with and without encapsulated PCM immersed in grape must are described. A global energy equation accounting for heat generated by fermentation and heat exchange by vessel walls was applied. fermentation with PCM shows a slower temperature increase compared to the control. While the control hits 30 °C in about 50 h, the PCM fermentation approaches this over 30 h later, peaking at 29.5 °C on average. This results in an average fermentation temperature of 24 °C with PCM versus 27 °C for the control, indicating PCM's effectiveness in absorbing fermentation heat and maintaining temperatures below the 30 °C target. Potential applications in winemaking for improved temperature management are proposed.